The C5-75 Program: Meeting the Need for Efficient, Pragmatic Frailty Screening and Management in Primary Care. Issue 2 (23rd June 2021) - Lee, Linda; Jones, Aaron; Costa, Andrew; Hillier, Loretta M.; Patel, Tejal; Milligan, James; Pefanis, John; Giangregorio, Lora; Heckman, George A.; Parikh, Ruchi
ABSTRACT: Case-Finding for Complex Chronic Conditions in Seniors 75+ (C5-75) is a systematic approach to identify frailty using gait speed and hand-grip strength and to screen for co-morbid conditions. We identified the C5-75 features offering the highest yield for identifying frailty and to streamline the screening program. Analyses included 1, 948 C5-75 assessments completed from 2013 to 2018. Age 85 or older, less than regular physical activity, and more than two falls in the previous six months had the strongest associations with frailty. Exempting patients under 85 who reported regular physical activity and less than two falls excluded 39.1 per cent of the cohort while maintaining a sensitivity of 95.2 per cent and a negative predictive value of 99.4 per cent for frailty. These findings provide insight into optimizing screening for frailty, making it more feasible to implement and to identify co-existing conditions that may contribute to or be affected by frailty.